The Effect of Metformin on the Hypothalamic-pituitary-thyroid Axis in Patients with Type 2 Diabetes and Subclinical Hyperthyroidism - Krysiak, R.; Szkrobka, W.; Okopien, B. (Experimental and Clinical Endocrinology & Diabetes, 2015)
In hypothyroid patients, metformin was found to reduce serum levels of TSH. No previous study investigated metformin action on hypothalamic-pituitary-thyroid axis in patients with hyperthyroidism. The aim of our study was to assess the effect of metformin treatment on thyroid function tests in patients with untreated subclinical hyperthyroidism. We studied 15 patients with low but detectable TSH levels (0.1–0.4 mIU/L) (group 1), 12 patients with suppressed TSH levels (less than 0.1 mIU/L) (group 2) and 15 euthyroid patients with a history of hyperthyroidism, who because of coexisting 2 diabetes were treated with metformin (2.55–3 g daily). Glucose homeostasis markers, as well as serum levels of TSH and total and free thyroxine and triiodothyronine levels were assessed at baseline and after 3 and 6 months of therapy. As expected, metformin reduced plasma glucose, insulin resistance and glycated hemoglobin. However, with the exception of an insignificant decrease in TSH levels after 3-month therapy in group 2, metformin therapy did not affect thyroid function tests. Our results indicate that metformin has a negligible effect on hypothalamic-pituitary-thyroid axis activity in type 2 diabetic patients with subclinical hyperthyroidism.
Keywords: hyperthyroidism; diabetes mellitus; metformin; hypothalamic-pituitary-thyroid axis